MRI-Induced Neurosensory Events in Decorative Black Tattoos: Study by Advanced Experimental Methods - Kasper Køhler Alsing; Ole Olsen; Christian Bender Koch; Rasmus Hvass Hansen; Daniel Pergament Persson; Klaus Qvortrup; Jørgen Serup (Karger Publishers, 2023)
Adverse reactions in tattooed skin during magnetic resonance imaging (MRI) are rare but well known. Previous reports describe sudden burning pain in tattooed skin, sometimes accompanied by mild erythema and oedema when entering MRI scanners. The pathophysiology remains unclear, but simple direct thermal heating can be excluded. It has been hypothesized that MRI-triggered torque and traction create neural sensations from magnetic pigment particles. However, this case enlightens yet another possible mechanism. We present a 35-year-old woman experiencing reoccurring stinging sensations in three decorative black tattoos just seconds after the initiation of the MRI. Single-blind tests with handheld power magnets or a dummy could reproduce painful subjective feelings in her tattooed skin. Similar events were provoked during re-evaluation with MRI. Surprisingly, chemical analyses and electron microscopy of skin samples revealed carbon black as the colouring agent - no iron-based solids were detected. Our case demonstrates that MRI tattoo reactions are not limited to magnetic contaminants alone. More distinct subgroups of MRI-induced reactions may occur. We hypothesize that radiofrequency induction of surface currents in black carbon particles adjacent to sensory axons in the dermis may lead to neurosensations.